Procesamiento de semilla de algodón para producir aceite y proteína - Mayorga, Hector; González, Jaime; Arzu, Alberto; Rolz, Carlos (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Industrial level cooking and screwpressing experiments cottonseed are described. The conditions of cooking, drying and pressing were determined in order to obtain a cake of high protein quality without affecting substantially the yield of oil extraction. The best conditions determined were those of low temperature, cooking and drying. Under these conditions the largest drop in protein solubility take place during the cooking stage. With the purpose of increasing the inactivation of gossypol, tests were run under alkaline conditions, using NaOH and Ca(OH)2 and the best results were obtained with NaOH at pH of 8.0.